Evolution of Rosaceae Plastomes Highlights Unique Cerasus Diversification and Independent Origins of Fruiting Cherry - Zhang, Jing; Wang, Yan; Chen, Tao; Chen, Qing; Wang, Lei; Liu, Zhen-shan; Wang, Hao; Xie, Rui; He, Wen; Li, Ming; Liu, Cong-li; Yang, Shao-feng; et al. (Frontiers in Plant Science, 2021)
Rosaceae comprises numerous economically important fruits, ornamentals and timbers. The lack of plastome characteristics has blocked our understanding about the evolution of plastome and plastid genes of Rosaceae crops. Using comparative genomics and phylogenomics, we analyzed 121 Rosaceae plastomes of 53 taxa from 13 genera, predominantly including the Cerasus (true cherry) and its relatives. To our knowledge, we generated the first comprehensive map of genomic variation across Rosaceae plastomes. Contraction/expansion of inverted repeat regions and sequence losses of the two single-copy regions underlay large genomic size variations among Rosaceae plastomes. Plastid protein-coding genes were characterized with high proportion (over 50%) of synonymous variants and insertion-deletions with multiple triplets. Five photosynthesis-related genes were specially selected in perennial woody trees. Comparative genomic analyses implied divergent evolutionary patterns between pomaceous and drupaceous trees. Across all examined plastomes, unique and divergent evolution was detected in Cerasus plastomes. Phylogenomic analyses and molecular dating highlighted the relatively distant phylogenetic relationship between Cerasus and relatives (Microcerasus, Amygdalus, Prunus, Armeniaca), which strongly supported treating the monophyletic true cherry group as a separate genus excluding dwarf cherry. High genetic differentiation and distinct phylogenetic relationships implied independent origins and domestication between fruiting cherries, particularly between Prunus psuedocerasus (Cerasus pseudocerasus) and P. avium (C. avium). Well-resolved maternal phylogeny suggested that cultivated P. pseudocerasus originated from Longmenshan Fault zone, the eastern edge of Himalaya-Hengduan Mountains, where it was subjected to frequent genomic introgression between its presumed wild ancestors and relatives.